Manajemen Informasi Persediaan Obat Menggunakan Metode Fefo Di Apotik Semarang - Siswanto Siswanto; Oktaviani Br Surbakti (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This research was conducted at the Jatingaleh Pharmacy, Semarang, currently the pharmacy is still experiencing difficulties in terms of processing drug supplies, the obstacles experienced include recording drug supplies manually, which is recorded in a ledger then inputted into a computer. The system also has not been able to generate reports of drugs that are about to expire. This study aims to provide solutions to problems related to the drug supply system, and can produce reports of drugs that will enter expiration at the Jatingaleh Pharmacy Semarang. This research method uses a Research and Development (R&D) model approach with 6 stages, namely Research and information collecting, planning, developing preliminary form of product, preliminary field testing, main product revision, and main field testing. This system was created using Microsoft Visual Basic 6.0 programming language using SQL Server 2000 database and based on Multiuser. With the system design from this study, it is able to handle problems at the pharmacy, and can facilitate the performance of the pharmacy staff so that the work becomes faster and more efficient.